Effect of the Use of News-Based Science Teaching on Al Madani Pesantren Student’s Literacies (Universitas Negeri Semarang, 2018)
The development of information in the digital era and the technology progression have an impact on the easy access to information. Society tend to receive the information from sources that have not been accurate. Observation in IPA class on natural science subject is still based on the package books and LKS which provided by the school. Learning natural science through news increase the student involvement and support a lifelong learning. Thus the IPA teacher presents a model of news-based teaching at environmental pollution topic. The method used is a Quasi Experimental Design with the non-equivalent control group design. The population is seventh grade students in junior high school IT Al Madani. Sampling with cluster random were taken by two classes. The results showed the t-test different significant (sig value > 0,05). The increase literacy in science class experiment were 49,2%, while the control class were 36,0%. Critical thinking ability of students have a different significant (sig value > 0,05). The ability of critical thinking students class experiments were 28,3%, while control class were 21,7%. Model news-based teaching familiarize students to think seamlessly and original then develop the creativity. Creativity in the experiment class were more develop than the control class. Creativity in the form of written ideas are the works of scientific posters, letters for officials, and recycle products. The conclusion were news-based teaching model influenced the science literacy, critical thinking, and creativity.